Approaches towards the Independency of the Administrative System of the Administrative Judiciary from the Administrative System of the Ordinary Judiciary (Justice) in Jordan: Applied Study for the Provisions of the Jordanian & French Legislation and Judiciary - Al-Billeh, Tareq Nicola (Dirasat: Shari'a and Law Sciences, 2020)
This research deals with the approaches towards the independency of the administrative system of the administrative judiciary from the administrative system of the ordinary judiciary in Jordan (applied study for the provisions of the Jordanian & French Legislation and Judiciary). This study aims at laying down the basic legal foundation for applying the administrative judiciary independence from the ordinary judiciary and banning the interference of the ordinary judiciary with the works of the administrative judiciary in all respects. In fact, the independency, from the special administrative aspect, is represented by laying down a judicial independence law concerned with the administrative judiciary that shall regulate the conditions for hiring administrative judges, transfering, delegation, and promoting them as well as the disciplinary penalties imposed on them. Actually, and as for the administrative legislator in France, then the same adopted the judicial duality for which it caused the administrative judiciary to be a judiciary independent from the ordinary judiciary in all respects in addition to regulating the conditions of hiring the administrative judges, transfering, delegation, and promoting them and the disciplinary penalties imposed on them according to the French Administrative Judiciary Law Hence. In this research, the nature of the administrative system independency of the administrative judiciary shall be approached in addition to approaching the legal situations concerned with all the administrative affairs of the administrative judges including the transfer, delegation, promotion and subjecting to disciplinary. Finally, the study concluded several conclusions and recommendation that were recited at the end of the research.